Spin clusters inside four young asteroid groups - Carruba, V [UNESP] (2020)
Asteroid groups may either form because of collisions or because of spin induced fission. Recently it has been shown that young spin clusters tend to form more frequently in young collisional families than in older groups. Here, we study the occurrence of spin clusters inside four very recently identified asteroid groups: the (525) Adelaide, (2258) Viipuri, (6142) Tantawi, and (18429) (1994 AO1) groups. Using combinations of techniques based on backward numerical simulations, we identify four spin pairs among the family members. All groups have fractions of observed spin clusters well above 5 per cent, so confirming an observed trend for other young asteroid groups. The (2258) Viipuri and (18429) (1994 AO1) groups are compatible with an origin as a spin clusters themselves, and could be other occurrences of cascade spin clusters, as recently detected in other asteroid groups. Finally, the separation between collisional asteroid families and spin clusters in domains of dispersion of proper semimajor axis, sigma(a), versus age seems to be more complex than previously thought. While spin clusters tend to be much more compact in proper elements than collisional families, there appears to be a transition region in sigma(a) where both the groups be found.